Perbandingan Nilai Hematokrit Sebelum dan Sesudah Terapi Tirosin Kinase Inhibitor pada Pasien Chronic Myeloid Leukemia - Muhammad Ihza Lisan Shidqi; Yanti Sunaidi; Eleventi Oktarina Putri; Antoni Aldo Danendra Sawal (Jurnal Analis Kesehatan Kendari, 2025)
Chronic Myeloid Leukemia (CML) is a hematologic malignancy characterized by the presence of the Philadelphia chromosome and the BCR-ABL1 fusion gene. Tyrosine kinase inhibitors (TKIs) have revolutionized CML management, improving patient survival and quality of life. However, evidence regarding the effect of TKI therapy on simple hematologic parameters, particularly hematocrit values, remains limited. This study aimed to analyze the differences in hematocrit levels before and after TKI therapy in patients with CML. A quantitative comparative design was conducted involving 53 CML patients (32 males, 21 females) aged 19–66 years. Hematocrit values were collected from medical records at two points: prior to therapy and after twelve months of TKI treatment. Data distribution was assessed using the Shapiro-Wilk test, and comparisons were performed using a paired sample t-test with a significance level of p < 0.05. The mean hematocrit value before therapy was 29.7%, increasing to 36.7% after therapy, with an average rise of 7.0%. Of the total patients, 42 (79.2%) showed an increase in hematocrit, while 11 (20.8%) demonstrated a decrease. Statistical analysis confirmed a significant difference between pre- and post-therapy values (p < 0.001). TKI therapy significantly improves hematocrit levels in CML patients, reflecting restored hematopoiesis and improved hematologic status. Hematocrit may serve as a practical and cost-effective parameter for monitoring therapy effectiveness, especially in healthcare settings with limited access to molecular testing.